Structural chemistry and the transcendental numbers φ, e and π - Bucknum, Michael J. (2015)
Certain number theory relations that emerge from considerations of the topological character of several patterns taken from structural chemistry are reviewed. These relations define the products e · π and φ ·e from topological considerations of the respective structural-types. We further present here an approximate number theory formula for the quotient π / φ and for the product φ · e · e · π that are derived from the earlier formulas based in structural chemistry.